An insight into the CO2 solubility in NaCl + ethylene glycol (1:16) deep eutectic solvent: experimental and modeling - Ali Rasoolzadeh; Mehdi Keshtkar; Sona Raeissi; Reza Haghbakhsh (Results in Engineering)
The regulation of CO₂ emissions from industrial operations is crucial from an environmental perspective. The most widely used solvents for CO₂ capture consist of aqueous alkanolamine solutions. However, amine-based processes face several challenges, such as corrosion, chemical degradation, and high energy requirements for solvent regeneration. As potential alternatives, deep eutectic solvents (DESs) have emerged as promising eco-friendly and biodegradable options for CO₂ capture. This study experimentally measures the solubility of CO₂ in a DES (1 mol NaCl + 16 mol ethylene glycol) using a high-pressure solubility apparatus at the four temperatures of 293.15, 303.15, 313.15, and 323.15 K. For the thermodynamic modeling, the Soave Redlich Kwong equation of state (SRK EoS) was employed, coupled with three different mixing rules of van der Waals (vdW), Wong Sandler (WS), and modified Huron-Vidal (MHV1). The vdW approach was considered in the three cases without using binary interaction, constant binary interaction, and variable binary interaction parameter by temperature. The results demonstrated that by incorporating the WS and MHV1, the local composition concept was successful in addressing the non-ideality of the liquid phase. Among the tested models, the WS (AARD%=6.66) and MHV1 (AARD%=5.61) provided the most accurate predictions of equilibrium pressures. Additionally, Henry's constant, standard Gibbs energy, enthalpy, and entropy of gas solvation were determined using the experimental data together with classical thermodynamic relations. The calculated negative standard enthalpy of solvation indicates an exothermic gas solvation process, signifying that energy is released as CO₂ dissolves in this DES.